Challenges Faced by Bangladeshi Migrant Workers in Gulf Countries: An Analysis of Discrimination, Harassment and Safety Concerns - Sadi, Sadi Mohamod; Akter, Asma; Utsha, Abdal Jalal Mohammed Musabbir (Academia Journal of Humanities & Social Sciences, 2025)
This study examines the experiences of Bangladeshi migrant workers in Gulf countries. The study focuses on discrimination, safety, support, healthcare, wages, and working conditions. Data were collected from 50 respondents via survey questionnaires. This revealed significant challenges that included widespread discrimination and inadequate living conditions, alongside variations in workplace security and legal assistance. Statistical analyses, including chi-square tests, confirm significant differences in safety concerns across countries. Differences in discrimination and harassment were not statistically significant. The findings highlight the need for improved labor protections for migrant workers in the host countries.